Adaptation to an amoeba host drives selection of virulence-associated traits and genetic variation in saprotrophic Candida albicans - Amsri, Artid; Pruksaphon, Kritsada; Thammasit, Patcharin; Nosanchuk, Joshua D.; Youngchim, Sirida (Frontiers in Cellular and Infection Microbiology, 2024)
Amoebae are micropredators that play an important role in controlling fungal populations in ecosystems. However, the interaction between fungi and their amoebic predators suggests that the pressure from predatory selection can significantly influence the development of fungal virulence and evolutionary processes. Thus, the purpose of this study was to investigate the adaptation of saprotrophic Candida albicans strains during their interactions with Acanthamoeba castellanii. We conducted a comprehensive analysis of survival after co-culture by colony counting of the yeast cells and examining yeast cell phenotypic and genetic characteristics. Our results indicated that exposure to amoebae enhanced the survival capacity of environmental C. albicans and induced visible morphological alterations in C. albicans, particularly by an increase in filamentation. These observed phenotypic changes were closely related to concurrent genetic variations. Notably, mutations in genes encoding transcriptional repressors (TUP1 and SSN6), recognised for their negative regulation of filamentous growth, were exclusively identified in amoeba-passaged isolates, and absent in unexposed isolates. Furthermore, these adaptations increased the exposed isolates' fitness against various stressors, simultaneously enhancing virulence factors and demonstrating an increased ability to invade A549 lung human epithelial cells. These observations indicate that the sustained survival of C. albicans under ongoing amoebic predation involved a key role of mutation events in microevolution to modulate the ability of these isolates to change phenotype and increase their virulence factors, demonstrating an enhanced potential to survive in diverse environmental niches.